Enhanced Green Upconversion Emission From α‐NaYF4:Yb, Er Nanoparticles Embedded Silica Inverse Opal Heterostructure. Issue 8 (9th May 2018) - Shrivastava, Vishnu Prasad; Kumar, Jitendra; Sivakumar, Sri
Abstract: Alfa (α)‐NaYF4 : Yb, Er nanoparticles embedded silica inverse opal heterostructure, with dual photonic stop bands and negligible local thermal effects, was fabricated. This material exhibited improvement in its upconversion efficiency and green emission purity. The heterostructure was designed and constructed with a stack of two inverse opals with different periodicity to possess dual photonic stop bands at wavelengths λ ≈410 and ≈660 nm with a passband in‐between (≈545 nm). Although the two photonic stop bands suppress two distant emission bands (blue: 2 H9/2 → 4 I15/2 and red: 4 F9/2 → 4 I15/2 transitions) simultaneously, the passband enhances the green emission bands corresponding to 2 H11/2 → 4 I15/2 and 4 S3/2 → 4 I15/2 transitions of Er 3+ ions. The process leads to realization of a pure green color. In addition, the local thermal effects induced by laser irradiation at the surface of the nanoparticles are largely suppressed by effective dissipation of heat as a result of the microporous nature of the inverse opal heterostructures. The reduced thermal effect in embedded nanoparticles is advantageous and shown to be responsible for the enhancement of green emission, the increase or decrease in the luminescence lifetime of Er 3+ ion 2 H11/2 and 2 H9/2 or 4 S3/2 and 4 F9/2 states, a faster luminescence rise time, and almost the same green‐to‐red intensity ratio with variation in laser power. Abstract : Green purifier : Alfa (α)‐NaYF4 : Yb, Er nanoparticles embedded silica inverse opal heterostructure can suppress two distant undesired emission bands attributable to Er 3+ ions (blue and red) with enhancement instead of the green emission band. The microporous structure of the inverse opals facilitates reduction of the local thermal effect of the embedded nanoparticles which leads to modified luminescence decay and rise lifetimes and improved color stability.